(untitled) (Journal of Contemporary Philology, 2023)
This article presents observations about the linguistic peculiarities of Macedonian, Albanian, and Turkish proverbs about women from a pragmatic, semantic and syntactic point of view. Proverbs and sayings build as a separate semiotic and linguistic microsystem, so their linguistic peculiarities are described as well as their position compared to other literary genres. The purpose of the paper is to investigate if Macedonian, Albanian and Turkish proverbs and sayings about women carry the same type of messages conveyed by different formal structures.